Submandibular cellulitis: report of the clinical case - Chumpítaz Cerrate, Víctor (2009)
Modern dental care and use of antibiotics for treatment of oral infections have made that head and neck odontogenic infections will be uncommon. To avoid acute airway obstruction, dentists must be able to recognize and treat fastly this condition. Here, we report a clinical case of a male 51 years old patient with a head and neck deep infection caused by surgical removal of the right mandibular third molar. It is showed clinical characteristics, diagnostic criteria and treatment of such infections.